Numerical and Experimental Investigation of Twin-Roll Casting of Aluminum–Lithium Strips - Grydin, Olexandr; Garthe, Kai-Uwe; Yuan, Xueyang; Broer, Jette; Keßler, Olaf; Králík, Rostislav; Cieslar, Miroslav; Schaper, Mirko (Light Metals 2023)

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A Non-Linear Mean-Field Debonding Model at Large Strains for the Analysis of Fibre Kinking in Ud Composites - Cheng, Chun; Song, Chunlei; Mahnken, Rolf; Yuan, Zhipeng; Yu, Liang; Ju, Xiaozhe

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Individualization of Public Transport – Integration of Technical and Social Dimensions of Sustainable Mobility - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas; Weyer, Johannes; Cepera, Kay; Adelt, Fabian (Towards the New Normal in Mobility)
In order to follow the 1.5 degree path of the Paris Climate Agreement, drastic greenhouse gas reduction measures are needed in the transport sector. The potential of public transport and new mobility services to reduce transport-related greenhouse gas emissions cannot yet be fully exploited, especially in rural regions. This paper presents the concept of an innovative mobility system, called NeMo.bil, that intends to fill the gap between individual and public transport to create a demand-oriented and sustainable mobility offer. The concept is based on convoy formation of autonomously driving lightweight vehicles serving the first and last mile and a larger towing vehicle carrying enough power and energy to move the convoy over longer distances at higher speeds. This combination of two different vehicles, intelligently controlled by a digital ecosystem, aims to significantly increasing energy, resource and cost efficiency. Based on an analysis of previous approaches for innovative mobility solutions, the concept is derived from a technical and sociological perspective and its potential for reducing energy demand is calculated.

Goal‐oriented adaptivity based on a model hierarchy of mean‐field and full‐field homogenization methods in elasto‐plasticity - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Comparative Study of the Influence of Heat Treatment and Additive Manufacturing Process (LMD & L-PBF) on the Mechanical Properties of Specimens Manufactured from 1.2709 - Gnaase, Stefan; Niggemeyer, Dennis; Lehnert, Dennis; Bödger, Christian; Tröster, Thomas (Crystals)
(1) This work answers the question of whether and to what extent there is a significant difference in mechanical properties when different additive manufacturing processes are applied to the material 1.2709. The Laser-Powder-Bed-Fusion (L-PBF) and Laser-Metal-Deposition (LMD) processes are considered, as they differ fundamentally in the way a part is manufactured. (2) Known process parameters for low-porosity parts were used to fabricate tensile strength specimens. Half of the specimens were heat-treated, and all specimens were tested for mechanical properties in a quasi-static tensile test. In addition, the material hardness was determined. (3) It was found that, firstly, heat treatment resulted in a sharp increase in mechanical properties such as hardness, elastic modulus, yield strength and ultimate strength. In addition to the increase in these properties, the elongation at break also decreases significantly after heat treatment. The choice of process, on the other hand, does not give either process a clear advantage in terms of mechanical properties but shows that it is necessary to consider the essential mechanical properties for a desired application.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Derivation of third order Runge–Kutta methods (ELDIRK) by embedding of lower order implicit time integration schemes for local and global error estimation - Mahnken, Rolf (Computational Mechanics)
Abstract Three prominent low order implicit time integration schemes are the first order implicit Euler-method, the second order trapezoidal rule and the second order Ellsiepen method. Its advantages are stability and comparatively low computational cost, however, they require the solution of a nonlinear system of equations. This paper presents a general approach for the construction of third order Runge–Kutta methods by embedding the above mentioned implicit schemes into the class of ELDIRK-methods. These will be defined to have an Explicit Last stage in the general Butcher array of Diagonal Implicit Runge–Kutta (DIRK) methods, with the consequence, that no additional system of equations must be solved. The main results—valid also for non-linear ordinary differential equations—are as follows: Two extra function calculations are required in order to embed the implicit Euler-method and one extra function calculation is required for the trapezoidal-rule and the Ellsiepen method, in order to obtain the third order properties, respectively. Two numerical examples are concerned with a parachute with viscous damping and a two-dimensional laser beam simulation. Here, we verify the higher order convergence behaviours of the proposed new ELDIRK-methods, and its successful performances for asymptotically exact global error estimation of so-called reversed embedded RK-method are shown.
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Integrating Prospective LCA in the Development of Automotive Components - Grenz, Julian; Ostermann, Moritz; Käsewieter, Karoline; Cerdas, Felipe; Marten, Thorsten; Herrmann, Christoph; Tröster, Thomas (Sustainability)
The development of automotive components with reduced greenhouse gas (GHG) emissions is needed to reduce overall vehicle emissions. Life Cycle Engineering (LCE) based on Life Cycle Assessment (LCA) supports this by providing holistic information and improvement potentials regarding eco-efficient products. Key factors influencing LCAs of automotive components, such as material production, will change in the future. First approaches for integrating future scenarios for these key factors into LCE already exist, but they only consider a limited number of parameters and scenarios. This work aims to develop a method that can be practically applied in the industry for integrating prospective LCAs (pLCA) into the LCE of automotive components, considering relevant parameters and consistent scenarios. Therefore, pLCA methods are further developed to investigate the influence of future scenarios on the GHG emissions of automotive components. The practical application is demonstrated for a vehicle component with different design options. This paper shows that different development paths of the foreground and background system can shift the ecological optimum of design alternatives. Therefore, future pathways of relevant parameters must be considered comprehensively to reduce GHG emissions of future vehicles. This work contributes to the methodological and practical integration of pLCA into automotive development processes and provides quantitative results.
Keywords: prospective LCA; life cycle engineering (LCE); lightweight design; automotive components; body parts; circular economy; steel; aluminum; hybrid materials; fiber metal laminates

NeMo.bil - Dekarbonisierung des Verkehrs mithilfe von Leichtbau-Fahrzeugschwärmen - Ostermann, Moritz; Behm, Jonathan; Marten, Thorsten; Tröster, Thomas (WerkstoffPlus Auto 13. Fachtagung für neue Fahrzeug- und Werkstoffkonzepte)

Mesh- and model adaptivity for elasto-plastic mean-field and full-field homogenization based on downwind and upwind approximations - Tchomgue Simeu, Arnold; Mahnken, Rolf (XI International Conference on Adaptive Modeling and Simulation)

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Intrinsic forming of hybrid parts made of laser-structured aluminium sheet and CFRP-Prepreg - Wu, Shuang; Freund, Jonathan; Delp, Alexander; Haubrich, Jan; Löbbecke, Miriam; Walther, Frank; Tröster, Thomas

Case Study III: Challenges of lightweight design, vehicles, and rescuers - Akbulut Irmak, Emine Fulya; Hanses, Hendrik; Horwath, Ilona; Tröster, Thomas (Climate Protection, Resource Efficiency, and Sustainable Engineering)

Evaluation of the effects of different heating strategies on the joining partners during infrared welding of black polyamides - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J.

Evaluation of Infrared Welded Joints of Short Fiber Reinforced Thermoplastics Using Digital Image Correlation - Schöppner, Volker; Gevers, Karina; Schraa, L.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Proceedings of the 2023 International Conference on Composite Materials)

Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen (QSS) von Thermoplasten - Schöppner, Volker; Arndt, Theresa (Joining Plastics)

Dielectric Heating in the Vulcanization Process of Rubber Extrudates - Schöppner, Volker; Petzke, J.

Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Simulation of Infrared Welded Short Fiber Reinforced Thermoplastic Parts based on Mori-Tanaka Homogenization Method - Schöppner, Volker; Gevers, Karina; Hoenen, N.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Advanced Structured Materials)

Verbesserung der Betriebspunktauslegung durch Schneckensimulation - Schöppner, Volker; Austermeier, Laura; Trienens, Dorte (Wissenschaftlicher Arbeitskreis Kunststofftechnik)

The main factors influencing glass fiber shortening in the processing of bulk molding compounds (BMC) - Moritzer, Elmar; Scholle, Maximilian

Optimizing the Processing Performance of a Single Screw Extruder Using Live Simulations Based on Real Time Experimental Data - Köllermeier, Jonas; Schöppner, Volker

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

The Wave Must Be Right - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Plastic Insights)

Vorspannkraftrelaxation bei der Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Belastungsgerechte Auslegung automobiler Leichtbaustrukturen aus pressgehärtetem Stahl und kohlenstofffaserverstärktem Kunststoff - Triebus, Marcel
Hybride Bauteile, welche aus Werkstoffen mit hohen spezifischen Festigkeiten bestehen, können zu einem signifikanten Leichtbau im Automobil beitragen. Diese Arbeit erforscht die hybride Kombination von pressgehärtetem Stahl und kohlenstofffaserverstärktem Kunststoff. Ausgehend von einer Analyse bestehender Karosseriestrukturen erfolgt ein Konzept für eine hybride B-Säule. Das Potential zur Gewichtsreduzierung durch das hybride Bauteilkonzept wurde dabei zu 57 % identifiziert, welches jedoch nur bei Sicherstellung einer intakten Grenzfläche erreicht wird. Zur Erlangung der Grenzflächenfestigkeit bei charakteristischen Belastungsprofilen wurde ein Verfahren zur Einbringung makroskopischer Formschlusselemente im Presshärteprozess entwickelt. Durch diese Formschlusselemente wird eine Steigerung der Scherfestigkeit der hybriden Komponenten von über 300 % erreicht. Die gewonnenen Erkenntnisse werden abschließend zur Auslegung einer hybriden B-Säule angewendet.

Analysis and Optimization of Joint Formation in Hybrid Compression Molding - Lückenkötter, Julian; Aydin, Simon; Marten, Thorsten; Tröster, Thomas

Einfluss von Infrarotschweißprozessparametern auf die quasistatische und zyklische Belastbarkeit von technischen glasfaserverstärkten Thermoplasten - Gevers, Karina; Töws, P.; Schraa, L.; Decker, J.; Schöppner, Volker; Uhlig, K.; Stommel, M. (11. Landshuter Leichtbau-Colloquium)

A NEW APPROACH FOR THE LOCAL DETERMINATION OF ENERGY INPUT IN CO-ROTATING TWIN SCREW EXTRUDERS BASED ON SCREW TORSION - Schöppner, Volker; Austermeier, Laura; Nordieker, A.

Development Of An Asymmetric Torque Model For The Two Screws Of A Twin Screw Extruder - Schöppner, Volker; Austermeier, Laura; Alsoud, A.

Auswirkungen unterschiedlicher Erwärmstrategien auf infraroterwärmte Polyphthalamide - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J. (Joining Plastics)

Devulkanisation schwefelvernetzender Elastomere im halbleitergestützten Mikrowellenverfahren - Schöppner, Volker; Petzke, J.

Numerical investigations of new low‐order explicit last stage diagonal implicit Runge–Kutta schemes with the finite‐element method - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Abstract Initial value problems can be solved efficiently by means of Runge–Kutta algorithms with adaptive step size control. Diagonally implicit Runge–Kutta (DIRK) methods are the most popular class among the diverse family of Runge–Kutta algorithms. In this paper, the novel class of low‐order explicit last‐stage diagonally implicit Runge–Kutta (ELDIRK) methods are explored, which combine implicit schemes with an additional explicit evaluation as an explicit last stage. ELDIRK Butcher tableaus are used to control embedded RK methods to obtain solutions of different orders. The lower‐order solution is obtained by classical implicit RK stages and the higher‐order solution is obtained by additional explicit evaluation. As a result, a significant reduction in computational cost is achieved by skipping the iterative solution of nonlinear systems for the additional step. The examination of the heat problem and the use of the innovative Butcher tableau in the finite‐element method are the main contributions of this work. Thus, it is possible to establish adaptive step size control for the new low‐order embedded methods based on an empirical method for error estimation. Two‐dimensional simulations are used to show an appropriate algorithm for the ELDIRK schemes. The new Runge–Kutta schemes' predictions of higher‐order convergence are confirmed, and their successful outcomes are illustrated.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Investigation regarding the correlation of the relative influences during the extrusion process of cast films on the residual melt quality - Schöppner, Volker; Trienens, Dorte

Material-Preserving Extrusion of Polyamide on a Twin-Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Schall, Christoph Wilhelm Theodor; Wanke, Sven; Kley, Marina (Polymers)

Modellierung der Feststoffförderung im Einzug von Nutbuchsenextrudern mit Hilfe von DEM-Simulationen - Brüning, Florian
Bei der Auslegung von Einschnecken-Plastifizierextrudern mit genutetem Einzug sind Simulationen ein gängiges Mittel, um zeit-, ressourcen- und kostenintensive experimentelle Untersuchungen einzusparen. Bestehende mathematisch-physi-kalische Berechnungsmodelle auf Basis analytischer Gleichungen weisen jedoch einige Annahmen und Vereinfachungen auf, die die Qualität der rechnerischen Vorhersage reduzieren können. Diese Arbeit liefert daher einen Beitrag, indem analytische Modelle zur Berechnung des Druck-Durchsatz-Verhaltens und der Antriebsleistung in genuteten Einzugszonen mithilfe von numerischen Simulatio-nen basierend auf der Diskrete-Elemente-Methode (DEM) überprüft werden. Es wird gezeigt, dass die Annahme eines gegendruckunabhängigen Durchsatzver-haltens sowie die Unterscheidung in form- und reibschlüssige Förderfälle ge-rechtfertigt ist. Die Annahme einer Blockströmung ist oft nicht gerechtfertigt, auch wenn dies nicht notwendigerweise zu Abweichungen in der Durchsatzberech-nung führt. Für die analytische Durchsatz- und Leistungsberechnung werden re-gressionsbasierte Korrekturfaktoren eingeführt, die die Vorhersagegenauigkeit steigern. Weiterführende Untersuchungen zeigen, unter welchen Bedingungen und mit welchen Maßnahmen sich der Durchsatz von genuteten Einzugszonen steigern lässt. Schließlich wird eine Methode zur Kalibrierung von DEM-Simula-tionen vorgestellt, mit welcher sich die Abbildungsgenauigkeit des tribologischen Verhaltens des Schüttguts erhöhen lässt.

Untersuchung der UVC-Bestrahlung als Oberflächenvorbehandlungsmethode von Polycarbonaten zur Erzeugung einer Verbundhaftung zu Flüssigsilikonkautschuken - Hartung, Michael

An approach for the numerical calculation of the non-isothermal pressure-throughput-characteristics of single screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of the influence of process and screw configurations on fiber length for recycled carbon fiber - Malatyali, Hatice; Schöppner, Volker; Hoemann, Theresa (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of shear rates in twin-screw extruder using CFD-simulation - Malatyali, Hatice; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Influence of fiber geometry and sizing on glass fiber breakage - Bürenhaus, Franziska Isabelle; Moritzer, Elmar (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Downwind and upwind approximations for mesh and model adaptivity of elasto‐plastic composites - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract The use of heterogeneous materials, such as composites with Prandtl‐Reuss‐type material laws, has increased in industrial praxis, making finite element modeling with homogenization techniques a well‐accepted tool. These methods are particularly advantageous to account for microstructural mechanisms which can be related to nonlinearities and time‐dependency due to elasto‐plasticity behavior. However, their advantages are diminished by increasing computational demand. The present contribution deals with the balance of accuracy and numerical efficiency of nonlinear homogenization associated with a framework of goal‐oriented adaptivity, which takes into account error accumulation over time. To this end, model adaptivity of homogenization methods is coupled to mesh adaptivity on the macro scale. Our new proposed adaptive procedure is driven by a goal‐oriented a posteriori error estimator based on duality techniques using downwind and upwind approximations. Due to nonlinearities and time‐dependency of the plasticity, the estimation of error transport and error generation is obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Finally, a numerical example illustrates the effectiveness of the proposed adaptive approach.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Verfahrensentwicklung zur einstufigen Herstellung von biegebelastbaren Hybridstrukturen im Fließpressprozess - Stallmeister, Tim
Hybridstrukturen bieten bei Anwendungen mit Biegebeanspruchung ein großes Leichtbaupotenzial, erfordern jedoch komplexe und zum Teil mehrschrittige Fertigungsverfahren. In dieser Arbeit wird ein Verfahren entwickelt, das auf Basis des Fließpressprozesses biegebelastbare Hybridbalken in einem Schritt herstellt. Dazu wird ein Versuchsträger entwickelt, der die Komplexität von Realbauteilen abbildet und für zerstörende sowie zerstörungsfreie Charakterisierungsmethoden geeignet ist. Der Versuchsträger besteht aus einer funktionalisierten Kernstruktur aus Glasfasermattenverstärktem Polypropylen und äußeren Metallgurten aus Stahl- und Aluminiumlegierungen, die mit einem Haftvermittlerfilm versehen sind. Anhand des Versuchsträgers wird ein Fließpresswerkzeug und eine instrumentierte Fertigungsanlage entwickelt, mit der die Hybridstrukturen prototypisch hergestellt werden. Zur Prozessoptimierung wird die Verbindung mechanisch und optisch auf Probenebene analysiert. Weiterhin erfolgen Bauteiluntersuchungen anhand von Dreipunktbiegetests, mit denen das strukturelle Verhalten der Hybridbalken charakterisiert wird. Es wird festgestellt, dass sich mit dem einstufigen Fließpressverfahren sehr gute Verbundfestigkeiten erzielen lassen. Die Temperatur- und Druckführung weisen dabei einen großen Einfluss auf das Ergebnis auf. Anhand der Bauteiluntersuchungen wird bestätigt, dass mit dem entwickelten Verfahren Hybridbalken in nur einem Schritt gefertigt werden können, die vergleichbare mechanische Eigenschaften zu Hybridstrukturkonzepten aus mehrschrittigen Fertigungsverfahren aufweisen.

Regenerative Energien für einen effizienten Betrieb von Presshärtelinien - Knorr, Lukas; Jungeilges, André; Pfeifer, Florian; Burmeister, Sascha Christian; Meschede, Henning

Possibilities of Sustainable Heating Methods for Press Hardening Processes - Jungeilges, André

Untersuchung energieeffizienter und serientauglicher Erwärmungsstrategien mittels resistiver Erwärmung für den Presshärteprozess - Kaiser, Maximilian Alexander; Reitz, Alexander; Konrad, Stefan; Meyer, Thomas; Marten, Thorsten; Tröster, Thomas (Workshop Warmblechumformung)
Bei der Herstellung materialeffizienter Bauteile aus presshärtbaren Stählen für den Leichtbau sind nachhaltige und energieschonende Produktionsverfahren ein wichtiger Bestandteil der industriellen Prozesskette. Mittels direkter resistiver Erwärmung basierend auf dem Jouleschen Gesetz können Platinen energieeffizient, flexibel, bedarfsgerecht und „On Demand“ erwärmt werden. Restriktionen des Verfahrens ergaben sich bisher aus den realisierbaren Platinengeometrien. Ferner fehlten serientaugliche Konzepte zur automatisierten Fertigung resistiv erwärmter Bauteile. Durch ein neuentwickeltes Verfahren wird die resistive Schnellerwärmung von komplexen, umformtechnisch optimierten Bauteilen ermöglicht, wodurch eine vielfältige industrielle Nutzung realisiert werden kann. Aus diesem Grund wurde das neue Verfahren zur energieeffizienten Erwärmung anhand des Presshärteprozesses untersucht. Dazu wurde das Verfahren zunächst auf Probenebene verifiziert und innovative Erwärmungsstrategien durch die Modifizierung des Stromflusses untersucht. Weiterhin wurden prozessnahe Umformversuche durchgeführt und analysiert. Der Fokus der Untersuchungen lag auf der Prozesstechnik insbesondere der Homogenität der Temperaturverteilung sowie den erzeugten mechanischen Eigenschaften der Bauteile.
Keywords: Presshärten; resistive Schnellerwärmung; Energieeffizienz

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Investigation of the Deposition Velocity Related Temperature Deviations for High Temperature Materials in the FDM Process - Moritzer, Elmar; Hecker, Felix; Knaup, Felix; Wächter, Julian (Proceedings of the 37th International Conference of the Polymer Processing Society (PPS-37))

A micropolar model accounting for asymmetric behavior of cold‐box sand in relation to tensile and compression tests - Börger, Alexander; Mahnken, Rolf (PAMM)
Abstract Cold‐box sand (CBS) belongs to the granular materials and consists of sand and a binder. The behavior of CBS is simulated with a micropolar model, whereby the additional degree of freedom of the model describes the rotation of the sand grains. The model is used to generate a shear band under pressure for three different meshes, where the force‐displacement curves of the three meshes converge so that no mesh dependence occurs. Another requirement of the model is the consideration of asymmetric behavior for compression and tension. Due to the additional degree of freedom the implicit implementation of the micropolar continuum is very time‐consuming. Therefore, an explicit implementation is considered as an alternative possibility. This paper compares the advantages and disadvantages of both methods and the results for both calculations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Polymorphic uncertainty in constitutive modeling of polymer composites at different scales - Penner, Eduard

Simplified numerical calculation of the isothermal, three-dimensional, Non-Newtonian flow characteristics of single-screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Calibration of a Contact Model for DEM Simulations of Grooved Feed Sections of Single Screw Extruders - Schöppner, Volker; Brüning, Florian (36th International Conference of the Polymer Processing Society (PPS-36))

The short-and long-term properties of welded high-temperature-resistant thermoplastics - Vogtschmidt, Sascha; Schöppner, Volker

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Analysis and modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Altepeter, Matthias; Wanke, Sven; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Conceptions and Feasibility Study of Fiber Orientation in the Melt as Part of a Completely Circular Recycling Concept for Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Tölle, Lisa; Greb, C.; Haag, M. (Journal of Composites Science)

Polypropylene Degradation on Co-Rotating Twin-Screw Extruders - Schöppner, Volker; Altepeter, Matthias; Austermeier, Laura; Wanke, Sven; Meinheit, Philipp (Polymers 2023)

Investigation of the Homogenization Performance of Various Faceted Mixers and Optimization with Regard to Mixing as well as Pressure Throughput Behavior - Schöppner, Volker; Frank, Maximilian

Design of a test bench for measuring the degradation behavior of plastics during processing - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (PPS36)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Material Characterization of Polypropylene and Polystyrene Regarding Molecular Degradation Behavior - Schöppner, Volker; Schall, Christoph Wilhelm Theodor (Materials)

Characterization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian (Welding in the World)

Determination of Correlations between Melt Quality and the Screw Performance Index in the Extrusion Process - Trienens, Dorte; Schöppner, Volker; Bunse, Robin (Polymers 2023)

Improvement of a method for the correction of wall slip effects within the rheological measurements of filled rubber compounds - Schöppner, Volker; Kleinschmidt, Dennis (SPE Polymers)

Wall Slip-Free Viscosity Determination of Filled Rubber Compounds Using Steady-State Shear Measurements - Brüning, Florian; Kleinschmidt, Dennis; Petzke, J. (Polymers)

Recycling-Ansatz für mehrkomponentige Kunststoffprodukte durch thermische Verbundtrennung - Schöppner, Volker; Austermeier, Laura; Brüning, Florian; Oldemeier, Jan Philipp; Brandt, O. (EXTRUSION)

Anvil-free ultrasonic welding for welding situations with one sided access - Schöppner, Volker; Arndt, Theresa (76th Annual Assembly of the International Institute of Welding (IIW))

Conformal Cooling at Low Cost - Moritzer, Elmar; Kartelmeyer, S.; Kringe, R.; Jaroschek, C. (Plastics Insights)

Advances In RTM Manufacturing Of Metal-FRP Hybrids By Self-Sealing And In-Mold Cleaning Techniques - Chalicheemalapalli Jayasankar, Deviprasad
The importance of fiber-reinforced plastics for lightweight construction applications is steadily increasing due to their outstanding weight-specific property values. However, a decisive disadvantage of these composite materials has so far been the high material and process costs, which is why fiber-reinforced plastics are almost exclusively used in small to medium-sized series. Optimization of manufacturing methods is of great importance to reduce the production cost. In this study, two concepts are proposed that can optimize vacuum assisted light resin transfer molding (VA-LRTM) further, leading to a possibility of fully automatic process. Conventional VA-LRTM methods are used to produce complex fiber-reinforced plastics (FRP) and hybrid components. Traditional molds used to produce components via VA-LRTM are sealed using polymer materials to prevent the leakage of matrix system. The seals undergo tremendous amounts of thermal, chemical, and mechanical loadings. Thus, sealings must be replaced in short intervals. In the current study, a concept where sealing is achieved by accelerating the curing of matrix system itself with the help of heating elements and catalysts resulting in a self-sealing approach is proposed. Another concern is mold surface contamination during component production. To address this, a modified automatic cleaning technique based on ultrasonic cleaning was proposed which can be integrated into the production line with minimum modification. Both the proposed concepts were validated and optimized using experiments, simulations, and analytical approaches by producing metal-FRP hybrid shafts.
Keywords: fiber-reinforced plastics; resin transfer molding; composites

In-Mold Assembly of Hybrid GMT-Steel Brake Pedals by Compression Molding - Chalicheemalapalli Jayasankar, Deviprasad; Stallmeister, Tim; Lückenkötter, Julian; Tröster, Thomas
Keywords: Compression Molding; Glass Mat Thermoplastics; Hybrid Brake Pedal

Testing and modeling blast loading of a sandwich structure cored with a bio-inspired (balanus) core - Tuzgel, Firat; Akbulut Irmak, Emine Fulya; Guzel, Erkan; Yucesoy, Atacan; Sahin, Selim; Tasdemirci, Alper; Guden, Mustafa (Thin-Walled Structures)
Keywords: Mechanical Engineering; Building and Construction; Civil and Structural Engineering

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Measurement of material degradation in dependence of shear rate, temperature, and residence time - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (Polymer Engineering and Science)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Influence of process parameters on the formation of inhalable fiber dust during shredding for mechanical recycling of fiber‐reinforced organo sheets - Hopp, Matthias; Tölle, Lisa (Journal of Applied Polymer Science)

Fiber Dust Formation during the Recycling of FRP - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe international)

Faserstäube beim FVK-Recycling - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe)

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Auswirkungen unterschiedlicher Erwärmstrategien auf die quasistatische und zyklische Belastbarkeit von infrarotgeschweißten, glasfaserverstärkten Thermoplastbauteilen - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P. (Joining Plastics)

A Reverse Engineering Approach for Calibrating Frictional Behavior of Contact Models for Numerical Simulation of Solids Conveying in Extruders - Schöppner, Volker; Brüning, Florian; Sommer, L.

Auswirkungen des Vorscherungseinflusses im Extrusionsprozess auf die rheologischen Kennwerte gefüllter Kautschukmischungen - Schöppner, Volker; Kleinschmidt, Dennis; Nillius, U.; Hopmann, C. (GAK)